International institutions in an uncertain environment: success and failure of regime formation in the context of complex policy issues - Dietz, Wolfgang (2015)
In a global risk society, two interlinked developments increase complexity on environmental policy issues: On the one hand, unilateral problem solving is often ineffective in a globalized world. On the other hand, many environmental issues themselves are becoming increasingly complex. States have addressed these challenges by forming international institutions and regimes to collectively deal with environmental problems. But why do states form international environmental regimes on some issues while they fail to do so on others? How do states deal with scientific uncertainty on complex environmental issues and to what extent can scientific uncertainty account for success or failure of regime formation process? This dissertation provides insights on regime formation on highly complex policy issues by theorizing on how scientific uncertainty frames actors' perception of an issue. It is argued that actors are tolerant towards uncertainty on some aspects of an issue while they are not on others. This argumentation is empirically tested against four cases of international regime formation, two successful ones and two failed regime formation processes. The dissertation finds evidence that actors are more tolerant towards scientific uncertainty if it only affects the assessment of benefits while costs are at the same time estimated to be low.
Keywords: Hochschulschrift